Implementation of Transceiver module for SDR system using ADALM PLUTO platform - P., Sowjanya.; P., Satyanarayana (International Journal of Engineering and Technology, 2018)
Software Defined Radio (SDR) provides a comprehensive radio communication platform, based on which new technology can be used through software update. This leads to a large-scale reduction in expansion costs and enables the product to maintain technology development. The SDR platform can be set up with an open, standard, and programmable hardware platform, based on which the functions of the radio can be perceived by adding appropriate software modules. In this platform, the transformation and expansion of the radio functions are done in a software version without the need for a modification of the equipment. Such software radio station can easily communicate with the current or upcoming radio stations. In this article, we analyze SDR evolution and various platforms and implement various modulation techniques with the aim of successfully transferring a message wirelessly over-the-air using ADALM-PLUTO SDR platform by Analog Devices.Â